Careful attunements: the choreographing of care and affective witnessing through media practices during, and after, crisis. (March 2022) - McGrane, Caitlin; Hjorth, Larissa; Akama, Yoko
This paper takes a design anthropology approach to understanding the learnings, challenges and opportunities Victorians adopted to choreograph practices of care in and through media practice during and after the Australian 2019–2020 bushfire crisis. In doing so, we frame our inquiry from a perspective of how individuals and communities care through media practice. The study weaves together experiences around informal and formal crisis communication media – such as the government's VicEmergency App, Australian and international news media and social media sharing – to map what we call the careful attunements of choreographing care.